Modelling the psychological and design attributes of innovative product using interpretive structural modelling. (2017) - Kumar, Shailendra; Talib, Faisal
The aim of this paper is to understand the dynamics between various psychological and design attributes and to develop a model for it that helps in designing innovative products. On the basis of published literature and survey of experts' opinion, the paper identifies 16 attributes consisting of ten psychological and six design attributes that affect the performance of the innovative product design. This research utilises interpretive structural modelling (ISM) methodology to develop a hierarchy-based model and to understand the contextual relationships among the attributes of innovative products design. The finding shows that there exists a group of attributes having a high-driving power and low dependence requiring maximum attention and of strategic importance, they are: 'self direction' and 'achievement' while another group consists of those attributes viz. 'innovative product' and 'cost' which have high dependence and are the resultant actions. The ISM approach applied in this research is useful in understanding the dynamics between various psychological and design attributes as well as performance of designers in the context of engineering design activity. The paper spotlights the huge role of psychology in engineering design, especially in the design of innovative and competitive mechanical products and is equally useful for the human resource and management professionals/researchers.